Simplified Analysis of Thermal Cracks in Low-Heat Portland Cement Concrete - Longlong Liu; Shangchuan Zhao; Jianda Xin; Zhenhong Wang (Advances in Civil Engineering)
This article introduces some experimental data from the compression test, the tension test, and the temperature stress test machine (TSTM) test for low-heat Portland (LHP) cement concrete with different fly ash (FA) content. With the proposed equations, the thermal cracks can be predicted with the TSTM test along with the mechanical properties. The higher FA content exhibits a lower hydration degree and a smaller adiabatic temperature rise. Although the FA content decreases the hydration heat and the strength at an early age, there are few influences on the relational expression between compressive strength and tensile strength. The proposed equations can also be applied to estimate the thermal cracks risk in LHP cement concrete. The cracking stress of LHP cement concrete in the temperature stress test is not only related to the tensile stress history but also connected to the compressive stress history. Considering the strength history, an analytical method for evaluating the cracking temperature difference was proposed. With the proposed method, only compressive strength can be used to estimate the thermal cracks risk for LHP cement concrete at different ages. It greatly simplifies the evaluation method of thermal cracks in low-heat Portland cement concrete. Furthermore, this evaluation method can also be applied to other types of concrete.